Handbook of indigenous education - McKinley, Elizabeth Ann; Smith, Linda Tuhiwai 1950- (Singapore Springer Nature Singapore Pte Ltd., 2019)
This book is a state-of-the-art reference work that defines and frames the state of thinking, research and practice in indigenous education. The book provides an authoritative overview of the subject in one text. The work sits within the context of The UN Declaration of the Rights of Indigenous Peoples that states "Indigenous peoples have the right to the dignity and diversity of their cultures, traditions, histories and aspirations which shall be appropriately reflected in education" (Article 14.1). Twenty-five years ago a book of this nature would have been largely written by non-Indigenous researchers about Indigenous people and education. Today Indigenous researchers can write this work about and for themselves and others. The book is comprehensive in its coverage. Authors are drawn from various individual jurisdictions that have significant indigenous populations where the issues include language, culture and identity, and indigenous peoples participation in society. It brings together multiple streams of research by 'new indigenous voices. The book also brings together a wide range of educational topics including early childhood education, educational governance, teacher education, curriculum, pedagogy, educational psychology, etc. The focus of one body of work on Indigenous education is a welcome enhancement to the pursuit of the field of Indigenous educational aspirations and development.
Includes bibliographical references and index.
Keywords: Indigenous peoples -- Education -- Handbooks, manuals, etc; Indigenous peoples -- Education